Neuromyelitis Optica: A Diffusional Kurtosis Imaging Study - Doring, T.M.; Lopes, F.C.R.; Kubo, T.T.A.; Tukamoto, G.; Kimura, M.C.; Strecker, R.M.; Domingues, R.C.; Gasparetto, E.L. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Conventional MR imaging typically yields normal images of the brain or indicates lesions in areas of high aquaporin expression in patients with neuromyelitis optica. Diffusional kurtosis imaging was applied in patients with neuromyelitis optica to determine whether this technique could detect alterations in diffusion and diffusional kurtosis parameters in normal-appearing white matter and to explore the relationship between diffusional kurtosis imaging and DTI parameters. MATERIALS AND METHODS: Thirteen patients with neuromyelitis optica and 13 healthy controls underwent MR imaging of the brain with conventional and diffusional kurtosis imaging sequences. Tract-based spatial statistics and region-of-interest-based analyses were conducted to identify differences between patients with neuromyelitis optica and controls through conventional DTI and diffusional kurtosis imaging parameters. The parameters were correlated to determine the potential relationship between them. RESULTS: Compared with healthy controls, several diffusional kurtosis imaging and DTI parameters were altered in various fiber tracts of patients with neuromyelitis optica (P < .05). A significant decrease (P < .05) in radial kurtosis was observed in the corpus callosum and anterior corona radiata and left optic radiation. Differences (P < .1) in mean kurtosis were found in patients with neuromyelitis optica. We found a negative correlation between diffusional kurtosis imaging (radial kurtosis, axial kurtosis, mean kurtosis) and the corresponding DTI parameters (radial diffusivity, axial diffusivity, mean diffusivity). Positive correlations were found for radial kurtosis and mean kurtosis with fractional anisotropy. CONCLUSIONS: This study demonstrated differences in conventional diffusion and diffusional kurtosis parameters, especially radial kurtosis, in the normal-appearing white matter of patients with neuromyelitis optica compared with healthy controls. Larger studies of patients with neuromyelitis optica should be performed to assess the potential clinical impact of these findings. ADaxial diffusivityAKaxial kurtosisCCcorpus callosumDKIdiffusional kurtosis imagingFAfractional anisotropyMDmean diffusivityMKmean kurtosisNMOneuromyelitis opticaORoptic radiationRDradial diffusivityRKradial kurtosisTBSStract-based spatial statistics